Optimalisasi Social Media Engagement melalui Praktik MSDM di DPRD Kota Surabaya - Aji, Gagas; Nafie, Gustina Angen (Jurnal Akuntansi, Manajemen dan Ekonomi, 2025)
Social media is a critical tool for public institutions to enhance transparency, accountability, and citizen engagement. This study analyzes the effectiveness of the social media team at DPRD Kota Surabaya, focusing on content strategy, team competencies, and compliance with Law No. 14/2008 on Public Information Disclosure (UU KIP). Using a mixed-methods approach, quantitative data from Virol analytics and qualitative insights from interviews and document analysis were examined. Findings reveal an overreliance on image posts (202 posts, 12 likes, 1 comment per post), despite videos (30 likes per post) and albums (23 likes per post) demonstrating significantly higher engagement. This misalignment between content strategy and audience preferences is compounded by skill gaps, workload imbalances, and reliance on interns for content creation. However, the recent recruitment initiative for specialized content controllers marks a strategic shift toward professionalization. The study recommends prioritizing high-performing content formats (videos and albums), implementing structured training programs, balanced task distribution, and data-driven decision-making. Aligning social media practices with analytics insights and institutional objectives is essential to transform @setwankotasby’s Instagram into a platform that fosters trust, transparency, and meaningful public engagement